The Role of Easy Songs by JVKE in Improving Vocabulary Learning among Beginners - Deni Kurniawan; Felda Ratimaya; Cici Situmorang; Iyos Munidah Tussahihah; Sallammatul Ummah (Journal of Innovative and Creativity, 2026)
Vocabulary mastery is a major challenge for beginner-level English as a Foreign Language (EFL) learners, especially when the teaching methods tend to be monotonous. This study aims to explore the effectiveness of the song "Easy" by JVKE as a learning medium to improve the mastery of nouns through the fill-in-the-blank method. This study employed a descriptive qualitative approach, involving students from the English Education Study Program at Institut Prima Bangsa as participants. Data were collected through in-depth interviews and song-based vocabulary tests. The results showed that using the song "Easy" was able to increase motivation, reduce learning anxiety, and create a positive attitude toward English learning. The findings indicate that vocabulary acquisition occurred incidentally, where students more easily remembered repetitively appearing vocabulary such as "relationship," "door," and "pride." The fill-in-the-blank method proved effective in increasing students' active engagement and focus on the auditory context. However, the study also noted that while songs significantly aid memory retention, beginner learners still require explicit support from instructors to understand abstract vocabulary. In conclusion, the song "Easy" by JVKE is an effective medium for reinforcing basic vocabulary and student engagement, but its use is most optimal when combined with structured linguistic explanations.